Turning Stability in Individuals With Parkinson Disease. Issue 4 (October 2018) - Conradsson, David; Paquette, Caroline; Franzén, Erika
Abstract : Background and Purpose: Although instability during turning is a disabling feature of Parkinson disease (PD), little is known about the associated postural characteristics. Our goals were to compare turning stability between individuals with PD and healthy individuals and to investigate whether dopaminergic medication improves turning stability. Methods: Nineteen older adults with mild to moderate PD and 19 healthy individuals walked straight or walked and turned 180° to the right or left. The turning direction was visually cued before (preplanned) or during (unplanned) straight walking. Participants with PD were assessed off and on medication. As a proxy for mediolateral stability, we calculated the difference between pelvis lateral displacement and the lateral edge of the support base. Results: While healthy individuals regulated mediolateral stability in a steady-state manner during turning, mediolateral stability in PD was reduced for crossover steps (narrow steps by the foot contralateral to the turning direction) and increased for side steps (widening steps by the foot ipsilateral to the turning direction) ( P ⩽ 0.008). Individuals with PD turned with narrower step width ( P ⩽ 0.024) and smaller pelvis displacement than healthy individuals ( P ⩽ 0.002). Dopaminergic medication only improved mediolateral stability while using side steps to initiate unplanned turns ( P < 0.001). Discussion and Conclusions: Turning stability was compromised in PD, but only for crossover steps with a narrow support base. As dopaminergic medication showed limited effect on turning stability, rehabilitation plays an important role to promote safe turning strategies with a specific emphasis on sustainment of a wide support base. Video Abstract available for more insights from the authors (see Video, Supplemental Digital Content 1, available at:http://links.lww.com/JNPT/A236 ). Abstract : Supplemental Digital Content is Available in the Text.